Case Report: Uncommon complications of central catheters in newborns: two cases of parenteral nutrition extravasation - Coramusi, Carolina; Toro, Jessica F.; Pabón, Ramón G.; Barreto, Mario; Di Nardo, Giovanni; Parisi, Pasquale; Marín, Claudia C. M. (Frontiers in Pediatrics, 2025)
Central venous catheters (CVCs) are essential in neonatal care units to ensure prolonged venous access. Despite experienced CVC placement, managing fragile and small newborn vessels involves the risk of traumatic and iatrogenic complications. The most common include phlebitis, thrombosis, sepsis, and catheter displacement. Rarely, catheter displacement may lead to fluid accumulation around serous membranes and adjacent organs, which, if not identified early, can even result in neonatal death. We report two cases: one of neonatal hydrothorax with subsequent lung cystic formation after a parenteral nutrition leakage caused by the displacement of an Epicutaneo-Caval Catheter in the basilic vein of the left arm; the second involves a peritoneal collection of parenteral nutrition from the umbilical venous catheter.